UNCHARTED THRESHOLDS FOR A FLEDGED CHILD AND YOUTH CARE PROFESSION - Swanzen, Rika (International Journal of Child, Youth and Family Studies)

(untitled) (University of Victoria, 2024)
In the child and youth care sector, protecting vulnerable children is a key priority, one that requires a skilled workforce capable of meeting diverse and complex needs. Starting with an acknowledgement of the field’s struggle for identity, this article briefly recounts highlights of our journey to achieving recognition as a profession, with an emphasis on the South African context. The profession’s early phase is described along with the key developments that have shaped the scope of practice, leading to a discussion of current matters that have the potential to transform the field, and ideas regarding priorities that may need to be considered for a longer-term agenda. Reflections on a journey that builds on lessons from South Africa as they connect to a wider global context are shared. The initiatives shared within this journey reflect a resilient sector that has contributed to the creation of employment opportunities for child carers. They also provide some milestones for the formalising of a sector that requires regulation because of the vulnerable population it serves. From the emerging priorities, pointers for the next steps in the profession’s journey are offered.